SAT0122 Common and Specific Risk Factors for Cardiovascular Disease Among 6 Immune-Mediated Inflammatory Diseases: A Cross-Sectional Analysis. (9th June 2015) - Rodriguez-Rodriguez, L.; Perrotti, P.P.; Aterido, A.; Tornero, J.; Ferrandiz, C.; Cañete, J.D.; Fernandez-Nebro, A.; Gisbert, J.P.; Domènech, E.; Lόpez-Lasanta, M.; Marsal, S.; Fernández-Gutiérrez, B.
Abstract : Background: Immune mediated and inflammatory diseases (IMIDs) such a rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), psoriasis (Ps), and psoriatic arthritis (PsA), are associated with higher rates of cardiovascular (CV) morbidity and mortality, mostly due to accelerated atherosclerosis. Classic CV risk factors do not fully account for the gap observed in the prevalence and incidence of CV disease, when compared to that of the general population. Objectives: To analyze the influence of different demographic and clinical variables in the prevalence of CV disease in subjects affected with RA, PsA, Ps, SLE, or inflammatory bowel disease. Additionally, we compared the adjusted prevalence of CV disease among these conditions. Methods: Subjects included in this cross-sectional study were collected as part of the Immune-Mediated Inflammatory Disease Consortium (IMIDC) between 2007 and 2010. Demographic, disease and cardiovascular related clinical data was collected using a standard protocol of questionnaires, after a clinical interview with close questions and review of medical records. Bivariate and multivariate logistic and mixed-effects logistic regression models were performed for each condition, and the overall IMIDC, respectively. Standardize prevalence (SP) for each IMID was calculated using marginal analysis. Results: 9951 patients were included. When analyzed separately, traditional CV risk factors had a different contribution to CV disease in each IMID. Overall, when analyzed all subjects, older age at study, longer elapsed time from IMID diagnosis to study, presence of traditional CV risk factors (arterial hypertension, type2 diabetes mellitus, dyslipidemia, obesity) and male gender were independently associated with a higher CV disease risk. After adjusting by demographic and traditional CV risk factors, SLE exhibited the highest SP, followed by RA and Ps/Crohn's disease. Conclusions: Cardiovascular disease is related to immune-mediated inflammatory diseases. A different impact is shown dependent of particular disease directly affecting the burden of disease. Acknowledgements: We would like to thank all the patients and physicians for their collaboration. Disclosure of Interest: None declared